2019
DOI: 10.1007/s10751-019-1633-4
|View full text |Cite
|
Sign up to set email alerts
|

In-situ growth of iron mononitride thin films studied using x-ray absorption spectroscopy and nuclear resonant scattering

Abstract: We studied the structural and magnetic properties of in-situ grown iron mononitride (FeN) thin films. Initial stages of film growth were trapped utilizing synchrotron based soft x-ray absorption near edge spectroscopy (XANES) at the N K-edge and nuclear resonant scattering (NRS). Films were grown using dcmagnetron sputtering, separately at the experimental stations of SXAS beamline (BL01, Indus 2) and NRS beamline (P01, Petra III). It was found that the initial stages of film growth differs from the bulk of it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 86 publications
1
5
0
Order By: Relevance
“…As described above, the N K-edge spectra of bulk-like Fe-N film (thickness >1000 Å ) matches very well with ZB-type Fe-N film (Niti et al, 2020). In several reports it has been emphasized that the Fe-N phase is formed when Fe is sputtered in a pure N 2 plasma atmosphere (Niti et al, 2020;Gupta et al, 2019Gupta et al, , 2011Tayal et al, 2015). Therefore, the formation of the Fe-N phase can also be expected in the present work as the deposition was performed under similar conditions.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…As described above, the N K-edge spectra of bulk-like Fe-N film (thickness >1000 Å ) matches very well with ZB-type Fe-N film (Niti et al, 2020). In several reports it has been emphasized that the Fe-N phase is formed when Fe is sputtered in a pure N 2 plasma atmosphere (Niti et al, 2020;Gupta et al, 2019Gupta et al, , 2011Tayal et al, 2015). Therefore, the formation of the Fe-N phase can also be expected in the present work as the deposition was performed under similar conditions.…”
Section: Discussionsupporting
confidence: 70%
“…These test samples were then employed for X-ray reflectivity and X-ray diffraction measurements (using Bruker D8 Advance with Cu K X-rays) to obtain the deposition rates and structural information, respectively. From our earlier studies, it was found that reactive sputtering with nitrogen alone results in the formation of FeN (Gupta et al, 2019), CoN (Gupta et al, 2020) and Ni 2 N (Pandey et al, 2021) phases. N K-edge XANES of bulk-like ($ 1500 Å thick) Fe-N, Co-N and Ni-N thin film samples are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Since TEY mode is surface sensitive, samples were sputtered to remove about 20 nm of top layer using a 5 KeV, 50µA Ar + source incident at an angle of 45 • . Comparing the sputtered and in-situ grown N K-edge spectra 38 , it can be anticipated that sputtering of FeN sample does not severally affect the integrity of atomic arrangement in FeN sample. Local magnetic structure of samples was investigated using Mössbauer spectroscopy (MS) carried out at 300 K and also at low temperature (100 K) using a liquid He cryomagnet.…”
Section: Methodsmentioning
confidence: 99%
“…The stability of both phases was confirmed theoretically, with some calculations indicating that the zinc blende structure is more stable, while the other opting in favor of the rock salt structure. , Experimentally, Eck et al observed that, for compounds with stoichiometry FeN x , the rock salt structure emerges with the nitrogen content x = 0.5–0.7, while the zinc blende structure appears for x = 0.91 . As far as thin FeN films are concerned, Pandey and Gupta et al reported a transition from the rock salt γ′′′ to the zinc blende γ′′ structure with increasing film thickness. , …”
Section: Introductionmentioning
confidence: 85%
“…Single-phase and single-crystal films are only possible for epitaxial growth on single-crystal substrates, such as MgO(001), Cu(001), Cu(111), LaAlO 3 (001), SrTiO 3 (001), or Ru(0001) thin film . The other relatively commonly occurring phases are the γ′′-FeN, ε-Fe 3‑x N and α′′-Fe 16 N 2 . The films representing ζ-Fe 2 N, α′-Fe 8 N, γ′′′-FeN, and w-FeN constitute very rare cases.…”
Section: Structure Of Iron Nitride Filmsmentioning
confidence: 99%